2020
DOI: 10.3390/jcm9030776
|View full text |Cite
|
Sign up to set email alerts
|

Breast Mammographic Density: Stromal Implications on Breast Cancer Detection and Therapy

Abstract: Current evidences state clear that both normal development of breast tissue as well as its malignant progression need many-sided local and systemic communications between epithelial cells and stromal components. During development, the stroma, through remarkably regulated contextual signals, affects the fate of the different mammary cells regarding their specification and differentiation. Likewise, the stroma can generate tumour environments that facilitate the neoplastic growth of the breast carcinoma. Mammog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…The DCIS TME shows a high variability in composition and collagen amounts and in the topological distribution of stromal cells, including fibroblasts [18][19][20][21]. In fact, high collagen deposition and high mammographic density (HMD) are closely related to increased risk of BrCa [22]. The transcriptional profile of fibroblasts present in HMD samples indicated that they are prone to over-activate stress response, inflammation, stemness and C-Jun N-terminal kinase 1(JNK1) pathway and expression patterns similar to those of CAFs in BrCa [23].…”
Section: Role Of Fibroblasts On Ductal Carcinoma In Situ Progressionmentioning
confidence: 99%
“…The DCIS TME shows a high variability in composition and collagen amounts and in the topological distribution of stromal cells, including fibroblasts [18][19][20][21]. In fact, high collagen deposition and high mammographic density (HMD) are closely related to increased risk of BrCa [22]. The transcriptional profile of fibroblasts present in HMD samples indicated that they are prone to over-activate stress response, inflammation, stemness and C-Jun N-terminal kinase 1(JNK1) pathway and expression patterns similar to those of CAFs in BrCa [23].…”
Section: Role Of Fibroblasts On Ductal Carcinoma In Situ Progressionmentioning
confidence: 99%
“…Risk factors in serum include free E 2 , insulin-like growth factor 1 (IGF-1), the ratio of IGF-1 to IGF binding protein 3 (IGFBP-3), single nucleotide polymorphisms, and breast intra-epithelial neoplasia. An increased breast density is associated with changes in the microenvironment (increased secretion of inflammatory molecules, cytokines, growth factors) that favor tumor growth [ 19 ], and with a reduced renal excretion of estrogens [ 20 ]. Estrogens stimulate the expression of genes involved in cell growth and inflammation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lean women have an increased risk of dense breasts, which is a strong risk factor for breast cancer [22], including interval breast cancer [23]. Biologically, mammographic density is associated with breast stroma composition [24] with dense areas especially associated with higher pro-tumor fibrillar collagen deposition [25]. Collagen can directly increase the matrix stiffness and indirectly modulate mammary fibroblast secretion of soluble factors such as transforming growth factor beta, insulin-growth factor, and epidermal growth factor to promote tumorigenesis [24], leading to tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Biologically, mammographic density is associated with breast stroma composition [24] with dense areas especially associated with higher pro-tumor fibrillar collagen deposition [25]. Collagen can directly increase the matrix stiffness and indirectly modulate mammary fibroblast secretion of soluble factors such as transforming growth factor beta, insulin-growth factor, and epidermal growth factor to promote tumorigenesis [24], leading to tumor progression. Determining associations between obesity and interval breast cancer, as performed in this current study, could inform future efforts to understand and target the influence of BMI and associated adipose tissue on the underlying tumor biology and or masking of interval breast cancers.…”
Section: Introductionmentioning
confidence: 99%